The Influence of Gamification and Rewards on Customer Loyalty in Z Generation with Moderating Role of Gender (Case Study on the Shopee Marketplace) - Mustikasari, Anita; Fista, Theresia Fitri Fidia; Wijaya, Tony; Wardana, Wardana (Management Analysis Journal, 2022)
This study was conducted to determine the effect of gamification and rewards on customer loyalty in Generation Z, moderated by gender. This research uses a quantitative survey method. The sampling technique that the writer uses is purposive sampling with a total sample of 150 respondents. The data collected in this study used an online questionnaire technique, and the data analysis technique was Linear Regression and Moderated Regression Analysis. The results of this study indicate that: (1) Gamification has a positive influence on customer loyalty, (2) The higher the effect of rewards will have a positive effect on customer loyalty, (3) Gamification and rewards each have a positive influence on customer loyalty, (4) There is a positive effect of gender, namely, strengthening the effect of gamification on customer loyalty. It regards the value of the regression coefficient on the interaction between gamification and gender, which has a value of 0.085. (5) There is a negative effect of gender in weakening the effect of rewards on customer loyalty. It regards the value by the value of the regression coefficient on the interaction between rewards and gender, which has a value of -0.076. Therefore, in making gamification, gender can be considered so that the gamification made can be by the wishes of consumers.